Investigating workplace bullying (WPB), intention to quit and depression among nurses in the Upper West Region of Ghana. - Emmanuel Dapilah; Andrews Adjei Druye (PLoS ONE)
Background Intention to quit among nurses is increasingly recognized as a serious predictor of voluntary turnover. Voluntary turnover on the other hand is a significant factor fueling the shortage of nurses globally which could partly be blamed on negative workplace behaviors including but not limited to workplace bullying. Even though the relationship between workplace bullying and the intention to quit has been studied extensively, little is known about these concepts among nurses in Ghana. Aim The purpose of this study was to establish the relationship between workplace bullying among nurses and their intention to quit the profession in the Upper West Region of Ghana. We also determined the relationship between workplace bullying and depression among nurses. Methods We employed a cross-sectional design with 323 nurses recruited through a multistage sampling technique. Data were collected using a structured questionnaire with a 98.5% (N = 318) response rate. Results Initial descriptive statistics indicate that 64.4% (n = 203) of the nurses had intentions of quitting the job while 52.1% (n = 164) were depressed at various degrees based on scores on the DASS-21. Further analysis shows a positive linear relationship between WPB and intentions to quit. WPB was also correlated positively with depression among the nurses. This implies that an increased incidence of bullying at work is associated with increased intention to quit and depression among the nurses. Conclusions With over 50% of the nurses in this study intending to quit their jobs, it would be incumbent on nurse managers and other leaders at these health facilities to reconsider the work environment, policies, and leadership to prevent actual voluntary turnover. Managers must also fashion pragmatic strategies aimed at reducing stress and promoting the health and well-being of the nurses.